Performance comparison among the major healthcare financing systems in six cities of the Pearl River Delta region, mainland China. - Martin C S Wong; Harry H X Wang; Samuel Y S Wong; Xiaolin Wei; Nan Yang; Zhenzhen Zhang; Haitao Li; Yang Gao; Donald K T Li; Jinling Tang; Jiaji Wang; Sian M Griffiths (PLoS ONE, 2012)
BACKGROUND: The healthcare system of mainland China is undergoing drastic reform and the optimal models for healthcare financing for provision of primary care will need to be identified. This study compared the performance indicators of the community health centres (CHCs) under different healthcare financing systems in the six cities of the Pearl River Delta region. METHODS: Approximately 300 hypertensive patients were randomly recruited from the computerized chronic disease management records provided by one CHC in each of the six cities in 2011 using a multi-stage cluster random sampling method. The major outcome measures included the treatment rate of hypertension, defined as prescription of ≥ one antihypertensive agent; and the control rate of hypertension, defined as systolic blood pressure levels <140 mmHg and diastolic blood pressure levels <90 mmHg in patients without diabetes mellitus, or <130/80 mmHg among patients with concomitant diabetes. Binary logistic regression analyses were conducted with these two measures as outcome variables, respectively, controlling for patients' socio-demographic variables. The financing system (Hospital- vs. Government- vs. private-funded) was the independent variable tested for association with the outcomes. RESULTS: From 1,830 patients with an average age of 65.9 years (SD 12.8), the overall treatment and control rates were 75.4% and 20.2%, respectively. When compared with hospital-funded CHCs, patients seen in the Government-funded (adjusted odds ratio [AOR] 0.462, 95% C.I. 0.325-0.656) and private-funded CHCs (AOR 0.031, 95% C.I. 0.019-0.052) were significantly less likely to be prescribed antihypertensive medication. However, the Government-funded CHC was more likely to have optimal BP control (AOR 1.628, 95% C.I. 1.157-2.291) whilst the privately-funded CHC was less likely to achieve BP control (AOR 0.146, 95% C.I. 0.069-0.310), irrespective of whether antihypertensive drugs were prescribed. CONCLUSIONS: Privately-funded CHCs had the lowest rates of BP treatment and control due to a variety of potential factors as discussed.